High Dynamic Range Pixel Array Detector for Scanning Transmission Electron Microscopy. (11th January 2016) - Tate, Mark W.; Purohit, Prafull; Chamberlain, Darol; Nguyen, Kayla X.; Hovden, Robert; Chang, Celesta S.; Deb, Pratiti; Turgut, Emrah; Heron, John T.; Schlom, Darrell G.; Ralph, Daniel C.; Fuchs, Gregory D.; et al.
Abstract: We describe a hybrid pixel array detector (electron microscope pixel array detector, or EMPAD) adapted for use in electron microscope applications, especially as a universal detector for scanning transmission electron microscopy. The 128×128 pixel detector consists of a 500 µ m thick silicon diode array bump-bonded pixel-by-pixel to an application-specific integrated circuit. The in-pixel circuitry provides a 1, 000, 000:1 dynamic range within a single frame, allowing the direct electron beam to be imaged while still maintaining single electron sensitivity. A 1.1 kHz framing rate enables rapid data collection and minimizes sample drift distortions while scanning. By capturing the entire unsaturated diffraction pattern in scanning mode, one can simultaneously capture bright field, dark field, and phase contrast information, as well as being able to analyze the full scattering distribution, allowing true center of mass imaging. The scattering is recorded on an absolute scale, so that information such as local sample thickness can be directly determined. This paper describes the detector architecture, data acquisition system, and preliminary results from experiments with 80–200 keV electron beams.